THE STRATEGIC ROLE OF EDUCATION SUPERVISION IN THE IMPLEMENTATION OF PUBLIC POLICY TOWARDS IMPROVING THE HUMAN DEVELOPMENT INDEX - Sholihah, Imro’atus; Nisa’, Qonitatun (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
The Human Development Index (HDI) is a key indicator in measuring the quality of human resources, with education as one of its main pillars. Public policy in the education sector aims to improve quality, access, and equity, yet its success largely depends on effective implementation at the ground level. In this context, educational supervision plays a strategic role as a bridge between national policies and practices at the school level. This study uses a qualitative approach with a case study method to examine the contribution of supervision to the effectiveness of education policy implementation oriented toward improving HDI. The findings indicate that supervision functions not only as a control mechanism but also as a means of continuous assistance and evaluation. Through supervision, implementation barriers can be identified and addressed contextually. Additionally, supervision enhances the professional capacity of teachers and school principals, strengthens school management, and builds educators’ confidence in adopting new policies.Collaborative and sustained supervision proves effective in improving the quality of learning and educational outcomes. However, the implementation of supervision still faces challenges, such as a limited number of supervisors, insufficient training, and inadequate budget support. Therefore, strengthening the supervision system is crucial to support the success of education policy and the sustainable improvement of HDI.